Generation of induced pluripotent stem cells from a Becker muscular dystrophy patient carrying a deletion of exons 45-55 of the dystrophin gene (CCMi002BMD-A-9 ∆45-55) - Aoife Gowran; Gabriella Spaltro; Federica Casalnuovo; Vera Vigorelli; Pietro Spinelli; Elisa Castiglioni; Davide Rovina; Stefania Paganini; Marina Di Segni; Cristina Gervasini; Patrizia Nigro; Giulio Pompilio (Stem Cell Research, 2018)
Becker muscular dystrophy (BMD) is a dystrophinopathy caused by mutations in the dystrophin gene on chromosome Xp21. BMD mutations result in truncated semi-functional dystrophin isoforms. Consequently, less severe clinical symptoms become apparent later in life compared to Duchenne muscular dystrophy. Dermal fibroblasts from a BMD patient were electroporated with episomal plasmids containing reprogramming factors to create the induced pluripotent stem cell line: CCMi002BMD-A-9 that showed pluripotent markers, were karyotypically normal and capable of trilineage differentiation. MLPA analyses performed on DNA extracted from CCMi002BMD-A-9 showed an in-frame deletion of exons 45 to 55 (CCMi002BMD-A-9 Δ45-55).